2018
DOI: 10.5194/cp-2018-167
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A large increase in the carbon inventory of the land biosphere since the Last Glacial Maximum: constraints from multi-proxy data

Abstract: Abstract. Atmospheric CO2 increased by about 90 ppm across the transition from the Last Glacial Maximum (LGM) to the end of the preindustrial (PI) period. The contribution of changes in land carbon stocks to this increase remains uncertain. Estimates of the PI-LGM difference in land biosphere carbon inventory (∆land) range from −400 to +1,500 GtC, based on upscaling of scarce paleo soil carbon or pollen data. A perhaps more reliable approach infers ∆land from reconstructions of the stable carbon i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 124 publications
(240 reference statements)
0
2
0
Order By: Relevance
“…If the system is assumed to be closed, given the low δ 13 C signature of terrestrial carbon (−22‰ to −25‰), and with the knowledge of the atmospheric CO 2 concentration, δ 13 CO 2 , and an estimate of global mean oceanic δ 13 C, total terrestrial carbon can theoretically be calculated using a simple mass balance approach. However, Jeltsch‐Thömmes et al () have shown that under the assumption of a closed system, estimates can be skewed because the accumulation of carbon in sediments, input fluxes from rock weathering, and the burial of consolidated sediments have been neglected. By considering these factors, Jeltsch‐Thömmes et al () suggest that the terrestrial carbon reservoir was ∼850 Gt C (median estimate) smaller during the LGM than preindustrial, compared to recent difference estimates of 300–400 Gt C (Menviel et al, ; Peterson et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…If the system is assumed to be closed, given the low δ 13 C signature of terrestrial carbon (−22‰ to −25‰), and with the knowledge of the atmospheric CO 2 concentration, δ 13 CO 2 , and an estimate of global mean oceanic δ 13 C, total terrestrial carbon can theoretically be calculated using a simple mass balance approach. However, Jeltsch‐Thömmes et al () have shown that under the assumption of a closed system, estimates can be skewed because the accumulation of carbon in sediments, input fluxes from rock weathering, and the burial of consolidated sediments have been neglected. By considering these factors, Jeltsch‐Thömmes et al () suggest that the terrestrial carbon reservoir was ∼850 Gt C (median estimate) smaller during the LGM than preindustrial, compared to recent difference estimates of 300–400 Gt C (Menviel et al, ; Peterson et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies point to the potentially important role of the ocean/sediment/lithosphere fluxes of organic matter and how the associated burial-nutrient feedback modifies the magnitude and time scales of the response in CO2 and other tracers to changes in the marine biological cycles (Wallmann et al, 2016;Roth et al, 2014;Jeltsch-Thömmes et al, 2018). (Tschumi et al, 2011), for example, quantify the implication of oceansediment-lithosphere coupling for an experiment where the ocean P inventory is increased.…”
mentioning
confidence: 99%